Early Maladaptive Schemas in Children Victims of Sexual Violence (Global Journal of Human-Social Science, 2024)
Sexual violence is characterized by sexual play, heterosexual or homosexual, that part of a probationer development earlier and/or more power and has the purpose of sexual stimulation or the use of another to obtain sexual pleasure. The schemes are developed as a result of experiments harmful childhood, for example, abuse situations. Considering therapy focused on schemes and the literature on sexual violence in children and adolescents, aimed to evaluate a 14 year old victim of sexual violence during childhood in the following aspects: 1. Identify early maladaptive schemas; 2. Identify the consequences of post-trauma 3. Check the behaviors and ways of coping current establishing a relationship with the sexual violence suffered. We performed a semi-structured interview and were administered the Young Schema Questionnaire Questionnaire and parenting styles. Found in the participant schemas of abandonment/instability, mistrust/abuse and dependence/incompetence with predominant coping strategies and hipercompensação resignation.
Keywords: maladaptativos schemes; children; sexual violence